The Gender Regime of Anti-Liberal Hungary - Fodor, Eva (Springer Nature, 2022)
This Open Access book explains a new type of political order that emerged in Hungary in 2010: a form of authoritarian capitalism with an anti-liberal political and social agenda. Eva Fodor analyzes an important part of this agenda that directly targets gender relations through a set of policies, political practice and discourse-what she calls "carefare." The book reveals how this is the anti-liberal response to the crisis-of-care problem and establishes how a state carefare regime disciplines women into doing an increasing amount of paid and unpaid work without fair remuneration. Fodor analyzes elements of this regime in depth and contrasts it to other social policy ideal-types, demonstrating how carefare is not only a set of policies targeting women, but an integral element of anti-liberal rule that can be seen emerging globally.